Reading Preferences across Genders of Undergraduate EFL Students in Indonesia - Milal, A. Dzo'ul; Jannah, Raudlotul; Sa'adah, Sufi Ikrima; Fitria, Andini Anugrah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Due to pandemics, students carry out their studies from home. They have more leisure time and are freer to do activities. In such a condition, questioning students’ commitment to reading to learn becomes relevant. The question is whether and to what extent the students do the reading activity, what they read, and whether their preferences are different based on their genders. This topic is inconclusively studied, especially in the context of EFL. Therefore, it seems important to conduct a study on this topic because the results might raise the effectiveness of teaching EFL. This study is a descriptive survey revealing students’ reading preferences to spend their leisure time based on gender differences. The subjects are undergraduate EFL students aged 19–23 years who study at the English Department in Indonesia. The data were collected by a questionnaire consisting of closed and open items. The responses were tallied, calculated, and tabulated. The findings show that female respondents favored reading more than males. Both genders tend to prefer reading social media to spend their leisure time. Female respondents are more likely to read e-books, while male respondents are more into the printed books. They do extensive reading to get knowledge more than to get pleasure. Although they are EFL learners, they prefer reading the sources in their native language because it is more accessible than in the target language. The reasons underlying those findings and pedagogical implications are also described at the end of the article.